Vulnerability Analysis of Episodic Beach Erosion by Applying Storm Wave Scenarios to a Shoreline Response Model - Kim, Tae-Kon; Lim, Changbin; Lee, Jung-Lyul (Frontiers in Marine Science, 2021)
Recently, because of the influence of climate change on sea level change, there has been growing concern regarding the erosion of beaches, which play a role in reducing the damage caused by coastal disasters. However, despite these concerns, a comprehensive understanding of the morphodynamic relationship between hazard factors and beach erosion is still lacking. Therefore, in this study, a vulnerability analysis of beach erosion was conducted by applying the shoreline response model (SLRM) of bulk model type, which identifies the physical characteristics of relevant coefficients based on the suspended sediment movement processes. To characterize wave energy incidence, storm wave scenario modeling and extreme wave analysis were conducted using wave data of 40 years on the east coast of Korea provided by the National Oceanic and Atmospheric Administration. A dimensionless mathematical function representing the storm wave scenario was proposed as a function of the peak wave height. In addition, to examine whether the beach vulnerability curve (BVC) obtained from the SLRM is valid, it was compared with the long-term shoreline observation data conducted at Maengbang Beach. For the past 9 years, sand sampling and shoreline observations were performed at Maengbang Beach about 5 times a year. However, since observations were performed in time intervals of several months, the direct comparison with model results was impossible, so a comparative analysis through statistical analysis of shoreline variability was performed. The variability of the shoreline for each reference point followed a normal distribution with a standard deviation of approximately 7.1 m. As a result of comparing the BVC results obtained from these statistical characteristics with those obtained from the model, significant similarity was shown in the high wave condition. Finally, the model was performed on two factors (mean wave height and peak wave height) which appear in SWSF and three factors (wave energy at breaking point, beach response factor and beach recovery factor) which appear in SLRM, and by analyzing the results, an approximate formula for the BVC is derived. This novel BVC approximation equation provides an intuitive understanding of the factors that affect beach vulnerability as well as their importance, and estimates the beach buffer section required to prevent coastal facilities from being damaged by erosion during a specific period. The results of this study can help limit reckless coastal development and mitigate erosion damage.